2021
DOI: 10.1021/acs.jproteome.1c00620
|View full text |Cite
|
Sign up to set email alerts
|

NMR-Based Metabolomics Revealed the Underlying Inflammatory Pathology in Reactive Arthritis Synovial Joints

Abstract: Reactive arthritis (ReA) is an aseptic synovitis condition that often develops 2–4 weeks after a distant (extra-articular) infection with Chlamydia, Salmonella, Shigella, Campylobacter, and Yersinia species. The metabolic changes in the synovial fluid (SF) may serve as indicative markers to both improve the diagnostic accuracy and understand the underlying inflammatory pathology of ReA. With this aim, the metabolic profiles of SF collected from ReA (n = 58) and non-ReA, i.e., rheumatoid arthritis (RA, n = 21) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…Conversely, elevated levels of glucose in serum were observed in ReA patients (Guleria et al, 2019). Regarding lactate, the product of anaerobic glycolysis, PsA patients showed higher levels than those observed in RA patients, while two studies showed opposite results in ReA patients (Guleria et al, 2019;Souto-Carneiro et al, 2020;Dubey et al, 2021).…”
Section: Spondyloarthritis Cases Vs Rheumatoid Arthritis Casesmentioning
confidence: 97%
See 4 more Smart Citations
“…Conversely, elevated levels of glucose in serum were observed in ReA patients (Guleria et al, 2019). Regarding lactate, the product of anaerobic glycolysis, PsA patients showed higher levels than those observed in RA patients, while two studies showed opposite results in ReA patients (Guleria et al, 2019;Souto-Carneiro et al, 2020;Dubey et al, 2021).…”
Section: Spondyloarthritis Cases Vs Rheumatoid Arthritis Casesmentioning
confidence: 97%
“…5 studies included JIA patients (Zeft et al, 2014;Stoll et al, 2016;Butbul et al, 2020;Vernocchi et al, 2020;Funk and Becker, 2021). 5 studies included ReA patients (Ahmed et al, 2019;Guleria et al, 2019;Li et al, 2019;Muhammed et al, 2020;Dubey et al, 2021). 2 studies included uSpA patients (Ahmed et al, 2019;Muhammed et al, 2020), 1 study included ERA patients (Stoll et al, 2016), 1 study included IBD-SpA (Berlinberg et al, 2021).…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations